BS EN IEC 62631-3-12. Dielectric and resistive properties of solid insulating materials. Part 3-12. Determination of resistive properties (DC Methods). Volume resistance and volume resistivity, method for casting resins (30th April 2021) - British Standards Institution,
No abstract available